Hubungan Kemampuan Berpikir Kritis Perawat Sebagai Prediktor Kegiatan Keselamatan Pasien - Ningrum, Evi Harwiati; Rahmawati, Ike Nesdia; Eriprianto, Kukuh; Ahsan , Ahsan; Putra, Kuswantoro Rusca (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
The ability to think critically regarding patient identification, administering blood transfusions, infection control, medication management, and fall and injury management. The ability to think critically is the basis for nurses in improving patient safety. The aim of this research is to analyze the relationship between nurses' critical thinking abilities as a predictor to patient safety activities. This research uses a cross sectional design.Researchers used The Nursing Critical Thinking in Clinical Practice to measure nurses' critical thinking abilities and Safety Care Activity to measure patient safety activities. Linear regression is used to analyze the relationship between critical thinking skills as a predictor of patient safety activities. The results of this study show that critical thinking skills are associated as a predictor of patient safety activities (p=<0.001). Every increase of one point in the critical thinking ability score increases 0.006 in the patient identification score (p=<0.001), 0.004 in the blood transfusion score (p=0.001), 0.005 medication (p<0.001), and 0.007 infection management and fall management (p<0.001). The conclusion of this research is that there is a relationship between critical thinking skills and patient safety activities. It is recommended that critical thinking skills be improved by implementing nursing rounds so that patient safety and the quality of nursing services improve.